Room temperature corrosion behaviour of plastically deformed AISI 304 stainless steel by friction stir welding in neutral and acidified chloride solutions. (3rd October 2022) - Naskar, Anirban; Bhattacharyya, Madhumanti; Raja, Krishnan S.; Charit, Indrajit; Darsell, Jens; Jana, Saumyadeep
ABSTRACT: Severe plastic deformation of 304L stainless steel plate was carried out by friction stirring under an isothermal tool temperature at 825°C. The friction stirred zone showed extensive grain refinement, high fraction of low angle grain boundaries due to dislocation rearrangement, Σ3 and Σ9 special grain boundaries and discrete Fe–Cr–Mn-rich particles. Electrochemical polarisation measurements were done on the base metal (BM) and friction stir welded (FSW) specimens in the neutral and acidified 3.5% NaCl solutions. The BM showed marginally better pitting resistance in the neutral chloride solution than the FSW because of a larger fraction of special grain boundaries, and larger grain size. Whereas in acidified 3.5% NaCl solution, the FSW showed better corrosion resistance than the BM. The surface film of the FSW had a lower impedance and a lower defect concentration than the BM indicating higher diffusivity of point defects in the FSW.